Parent's Contribution to Strengthening Moral Awareness of Student Religiosity Behaviour - Hendra, Hendra; Khozin, Khozin; Irwan, Irwan; Anwar, Saiful (Al-Hayat: Journal of Islamic Education, 2024)
Strengthening religiosity for students is a variable that is considered very important in enhancing character in madrasas. This research aims to explain the contribution of parents' role in parenting patterns and students' moral awareness towards students' religious behaviour. This research uses quantitative analysis using cause and effect relationships. The population in this study was 246 students. The research sample was 159 students using the Slovin formula. Data collection techniques use interviews, questionnaires and documentation. This research uses several assumption tests, including normality, heteroscedasticity and linearity, multicollinearity, and suitability of the regression model. The research results show an R-value of 0.545, which shows the level of reliability based on the Alpha value in the Medium category in the interval 0.4?0.70. The role of parents in providing motivation and moral awareness in shaping religious behaviour has a significant contribution, with an increase in the ability of 29.7%. Therefore, parents have an essential role in providing parenting patterns in the form of exemplary habituation to children to provide an awareness value so that children have good religious behaviour.